MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK PEMBELAJARAN IPS - Hasma Handayani; Adelina Hasyim; Riswandi Riswandi (Indonesia Journal of Educational Technology, 2017)
The aim of this study was to improve the quality of learning by analyzing and finding out accurately: (1) the design of the learning plan social studies material appearance of natural, social and cultural with the symptoms, learning model discovery, (2) the process of learning social studies using model discovery, (3) the process of evaluation of learning outcomes at the end of the learning activities.Results of the study are: (1) the manufacture of learning design begins with the needs of learners who do not understand the material prerequisites style appearance, social and cultural, continue preparing the purpose of learning is to identify natural features, social and cultural symptomatically and discovery strategy, (2) the learning process with learning model discovery increases the activity of learners in the learning, (3) evaluation of learning outcomes using a written test about the description of the validity of 0.88, 0.99 reliability, level of difficulty and the matter is being well received about the different power.Penelitian ini bertujuan untuk memperbaiki kualitas pembelajaran dengan menganalisis dan menemukan dengan tepat:(1) desain perencanaan pembelajaran IPS materi Kenampakan alam, sosial dan budaya dengan gejalanya, dengan model pembelajaran discovery,(2) proses pembelajaran IPS menggunakan model pembelajaran discovery,(3) proses evaluasi hasil belajar di akhir kegiatan pembelajaran. Hasil penelitian adalah: (1) pembuatan desain pembelajaran diawali dengan kebutuhan belajar peserta didik yang belum memahami materi prasyarat kenampakan ala, social dan budaya, dilanjutkan menyusun tujuan pembelajaran yaitu mengidentifikasi kenampakan alam, social dan budaya dengan gejalanya dan strategi discovery, (2) proses pembelajaran dengan model pembelajaran discovery meningkatkan aktivitas peserta didik dalam pembelajaran, (3) evaluasi hasil belajar menggunakan tes tertulis soal uraian dengan validitas 0,88, reliabilitas 0,99, tingkat kesukaran soal sedang dan daya beda soal diterima baik.Kata kunci: hasil belajar, IPS, model pembelajaran discovery.